2020
DOI: 10.7717/peerj.8932
|View full text |Cite
|
Sign up to set email alerts
|

Post-transcriptional regulation of several biological processes involved in latex production in Hevea brasiliensis

Abstract: Background Small RNAs modulate plant gene expression at both the transcriptional and post-transcriptional level, mostly through the induction of either targeted DNA methylation or transcript cleavage, respectively. Small RNA networks are involved in specific plant developmental processes, in signaling pathways triggered by various abiotic stresses and in interactions between the plant and viral and non-viral pathogens. They are also involved in silencing maintenance of transposable elements and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 70 publications
2
14
0
Order By: Relevance
“…We had previously identified 445 transcripts degraded by miRNAs [20]. In this study, we did not identify any targets that were post-transcriptionally regulated by TE-derived siRNAs, consistent with the literature, revealing only translation inhibition and miRNA mimicry.…”
Section: Post-transcriptional Activity Of Te-derived Sirnassupporting
confidence: 89%
See 4 more Smart Citations
“…We had previously identified 445 transcripts degraded by miRNAs [20]. In this study, we did not identify any targets that were post-transcriptionally regulated by TE-derived siRNAs, consistent with the literature, revealing only translation inhibition and miRNA mimicry.…”
Section: Post-transcriptional Activity Of Te-derived Sirnassupporting
confidence: 89%
“…These analyses are a valuable resource for comparative epi/genomics within the Euphorbiacae, and transposon tagging for designing clone-specific molecular markers in Hevea. We had already demonstrated that the natural rubber biosynthesis pathway is under post-transcriptional control [20]. This work shows that this biosynthesis pathway is also under transcriptional control with a major role of TEs, which are functionalized in the promoters of the genes involved in natural rubber biosynthesis.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations